Music Business and the Experience Economy The Australasian Case - Tschmuck, Peter; Pearce, Philip L.; Campbell, Steven; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Music Business and the Experience Economy is the first book on the music business in Australasia from an academic perspective. In a cross-disciplinary approach, the contributions deal with a wide-range of topics concerning the production, distribution and consumption of music in the digital age. The interrelationship of legal, aesthetic and economic aspects in the production of music in Australasia is also highlighted as well as the emergence of new business models, the role of P2P file sharing, and the live music sector. In addition, the impact of the digital revolution on music experience and valuation, the role of music for tourism and for branding, and last but not least the developments of higher music education, are discussed from different perspectives.
From Discord to Harmony: Connecting Australian Music and Business Through the Experience Economy -- Australian Copyright Regimes and Political Economy of Music -- New Music Production Modes and Indigenous Music in North Queensland and the Torres Strait -- Australian Independent Music and the Experience Economy -- Recorded Music Sales and Music Licencing in Australia, 2000-2011 -- P2P File-Sharing: How Does Music File-Sharing Affect Recorded Music Sales in Australia?- Digital Distribution Models Reviewed -- The Landscape of Musical Festivals in Australia -- The Influence of Dirty Pool on the Australian Live Music Industry -- Building Brands with Music -- Australian Music and Aussie Team Sports -- The Valuation of Music in Australia: A Chart Analysis 1988-2011 -- Enterprise Learning in Australasian Tertiary Music Education.
Keywords: Industrial management; Music; Culture—Study and teaching; Management; Law and economics; E-commerce.; Media Management; Music; Regional and Cultural Studies; Cultural Management; Law and Economics; e-Commerce/e-business.